What we Know so far about Myxovirus Resistance Protein A (MxA) as a Biomarker of Interferon-Beta Therapy in Patients with Multiple Sclerosis: a Systematic Review - Shojaeefar, Ehsan; Ghaffari, Mehran; Mohammadi, Mahan; Hosseini, Jalil; Omrani, Mir Davood (Archives of Men’s Health, 2020)
Introduction: Multiple sclerosis (MS) is one of the most common neurological disabling diseases in human societies with no complete cure. IFN-β has been proven to be an important advance in the MS treatment, but early identification of treatment failure is its major concern. Some researches revealed that MxA is an appropriate biomarker for predicting response to IFN-β, so we performed this study to evaluate the relationship between MxA level and response to INF- β treatment.Methods: International and internal databases were searched using “MxA”, “Myxovirus resistance protein A”, “IFN-β”, “interferon Beta”, “multiple sclerosis” and “MS keywords until October 2019. Inclusion criteria were original studies considering the MxA assays in MS patients under IFN-β therapy. Some reported cut-offs from partially the same settings (7 studies) were pooled using the weighted average. Finally, the overall statements of the included studies were compared and discussed to obtain a comprehensive conclusion about the clinical value of MxA assays in patient monitoring and designing their treatment plan. Results: A total of 456 articles were identified. The Screening was led to exclusion of 427 articles. Finally, 28 original studies met the inclusion criteria for this systematic review. Almost all studies have concluded that the MxA is significantly correlated with response to IFN-β therapy and also MxA expression is under the direct effect of Neutralizing antibody (NAb) against IFN-β. Reported cut-offs for MxA ranged from 3.3 to 6.3 NR and the weighted average of them was estimated to be 4.1 NR. Conclusion: It could be suggested that in patients under IFN-β therapy with an active disease which doesn’t fulfill the criteria for the breakthrough disease, MxA level can help to determine whether to continue the drug and follow up a patient or change the treatment regimen.